Pengaruh Kualitas Layanan Terhadap Kepuasan Mahasiswa Pada Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu Musi Banyuasin - Syaputra, Dadang (Universitas muhammadiyah palembang, 2015)
The aim of this research is finding the influence of serving quality to the student satisfaction in Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, Kabupaten Musi Banyuasin. Variables used are the student satisfaction (Y) and the serving quality (X), which developed into five sub variables, they are realibility (x1), responsiveness (x2), competence (x3), access (x4), courtesy (x5), communication (x6), credibility (x7), security (x8), understanding the customer (x9), dan tangibles (x10). The population of this research is all students in Sekolah Tinggi Imu Ekonomi Rahmaniyah Sekayu, Kabupaten Musi Banyuasin. They study in the academic year of 2014-2015. The data needed is primary which obtained by the instrument of questionnaire. The result show that variable of serving quality (X) has significant influence to the student satisfaction (Y). Following this, it is only realibility (x1) which has influence to student satisfaction (Y). Meanwhile, responsiveness (x2), competence (x3), access (x4), courtesy (x5), communication (x6), credibility (x7), security (x8), understand the custumer (x9), dan tangibles (x10), they are partially have a positive influence, but not significant to student satisfaction (Y).